ANALISIS NILAI MORAL DALAM NOVEL TANAH PARA BANDIT KARYA TERE LIYE - Azita; Sri Rahayu (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study aims to describe the moral values in Tere Liye’s novel *Tanah Para Bandit* based on Bertens’s theory, which encompasses responsibility, conscience, and duty. This study employs a qualitative approach using a descriptive method. The data source for this study is the novel *Tanah Para Bandit* by Tere Liye, published by Sabak Grip in 2023. The research data consists of narrative excerpts and dialogues containing moral values relevant to the study’s focus. Data collection was conducted through reading and note-taking, while data analysis utilized an interactive analysis model comprising data reduction, data presentation, and drawing conclusions. Data validity was ensured through careful observation and theoretical triangulation. The results revealed 33 instances of moral values, consisting of 13 instances of responsibility, 11 instances of conscience, and 9 instances of duty. Moral values related to responsibility emerged as the most dominant aspect, as demonstrated by the characters’ attitudes in fulfilling their duties, upholding their commitments, and taking responsibility for every decision made. Values of conscience were reflected through the characters’ inner struggles, empathy, and moral awareness in facing various issues, while values of duty were manifested through the performance of tasks, the upholding of justice, and commitment to the responsibilities entrusted to them. The results of this study indicate that the novel *Tanah Para Bandit* not only presents an engaging story but also contains relevant moral values that serve as a medium for character education and can be used as a reference in literature education and research on moral values in Indonesian literary works.